PENYELESAIAN SENGKETA KREDIT BARANG ELEKTRONIK PADA LAYANAN HOME KREDIT DI KOTA PAYAKUMBUH - Rahman Illahi; Syuryani Syuryani; Jasman Nazar (Ensiklopedia of Journal, 2023)
Technology and information are now driving increased development in all fields. One of the increases in national development is the development of industrial and trade activities, increasing industrial and trade activities resulting in an increase in the capital sector in business development. While not all entrepreneurs have sufficient capital to develop their business, this is where many transactions are created In everyday life in the form of credit or loans, the Agreement has a close relationship with the engagement as Book III of the Civil Code Article 1233 which mentions the occurrence of an engagement which suggests that the engagement arises from an agreement or law. This research method used in this study is descriptive, namely legal research on the enactment or implementation of normative legal provisions in action on every particular legal event that occurs in society.the results of research if someone has been late paying installments for 1-2 months will be contacted by the closest people such as family or relatives. If within that time has not paid the credit installment, it will be reported to the Financial Services Authority (OJK) and the OJK will conduct BI checking where the person can no longer make credit at any leasing or any bank. Based on the results of research at PT. Home Credit Indonesia, Dispute resolution in the event of default in the implementation of consumer financing agreements at PT. Home Credit Indonesia basically first attempts to resolve internally, namely through billing to consumers, if negotiations or mediation are unsuccessful, but if non-litigation settlement efforts fail, then litigation settlement efforts can be made, namely through civil lawsuits to the Court.